2013
DOI: 10.1007/s00415-013-7086-9
|View full text |Cite|
|
Sign up to set email alerts
|

LRRK2 G2385R variant carriers of female Parkinson’s disease are more susceptible to motor fluctuation

Abstract: The relation between the LRRK2 mutation and its effect on Parkinson's disease (PD) has always caught a lot attention. Recent studies found that the G2385R polymorphism of LRRK2 may increase the risk of PD in Asian populations. Here we tried to clarify the relationship between the LRRK2 G2385R variant and the clinical profiles including motor complication in Chinese PD patients. We identified the LRRK2 variant in the Chinese Han population in northern China and evaluated the relationship between the G2385R vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…These participants also more commonly had motor fluctuations. The finding of a higher frequency of motor fluctuations is consistent with prior work from other Chinese investigators . Recently a comparison between iPD and 3 LRRK2 risk variants seen in Asian populations (G2385R, R1628P, or S1647T) found that UPDRS motor scores worsened more rapidly in LRRK2 variant carriers after a disease duration of 4 years .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These participants also more commonly had motor fluctuations. The finding of a higher frequency of motor fluctuations is consistent with prior work from other Chinese investigators . Recently a comparison between iPD and 3 LRRK2 risk variants seen in Asian populations (G2385R, R1628P, or S1647T) found that UPDRS motor scores worsened more rapidly in LRRK2 variant carriers after a disease duration of 4 years .…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting that dyskinesias (in contrast to motor fluctuations) were not more common in LRRK2 G2385R PD. Prior work is conflicting on this topic, with 1 report suggesting increased frequency dyskinesias (albeit to a lesser extent than motor fluctuations) 27 and another not finding any increase in dyskinesias. The apparent discordance between dyskinesias and motor fluctuations could be specific to G2385R mutations or may reflect other aspects of genetic susceptibility in Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants, such as DRD3 G3127A in the dopamine receptor (DR) gene have been shown to be involved in L-dopa-induced dyskinesia (Comi et al, 2017 ). G2385R in LRRK2 was previously found to be significantly associated with motor complications in female PD patients (Gao et al, 2013 ). Our analysis demonstrated that G2019S or G2385R carriers tend to develop motor complications with significant differences, consistent with higher LEDD, relative to non-carriers (Cacabelos, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, 23 papers were selected for further full text review. Four papers were not case-control studies [2124]; one was a review [25]; four did not provide detailed genotype data [2629]. Finally, we identified fourteen eligible papers [720] including nineteen studies in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%